Higher expression of SIRT1 induced resistance of esophageal squamous cell carcinoma cells to cisplatin - Cao, Bin; Shi, Qintong; Wang, Wengong (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Background: High expression of Sirtuin type 1 (SIRT1) exists in some cancer cells. However, it is still unclear whether SIRT1 affects the sensitivity of esophageal cancer cells to cisplatin. This study was designed to explore the relationship between SIRT1 expression and resistance of esophageal squamous cell carcinoma (ESCC) cells to cisplatin and reveal the underlying mechanism. Methods: The tissue samples of 68 ESCC patients were collected from Nanjing Drum Tower Hospital, China. All the patients had undergone cisplatin based combination chemotherapy. The expression of SIRT1and Noxa in tissue samples were analyzed by quantitative real-time reverse PCR (qRT-PCR) and Western blot. Human ESCC cell line (ECa9706 cells) was cultured and a cisplatin-resistant subline (ECa9706-CisR cells) was established by continuous exposure to cisplatin at different concentrations. The expression of SIRT1 and Noxa in both cell lines was analyzed by qRT-PCR and Western blot. siRNA technology was utilized to down-regulate the SIRT1 expression in ECa9706-CisR cells. The influence of SIRT1 silence on sensitivity of ECa9706-CisR cells to cisplatin was confirmed using CCK-8 assay and flow cytometry. Furthermore, the level change of Noxa after SIRT1 silence in ECa9706-CisR cells was determined by qRT-PCR and Western blot. Result: SIRT1 and Noxa expression in chemo-resistant patients was significantly increased and decreased respectively, compared with chemo-sensitive patients. SIRT1 expression in ECa9706-CisR cells was significantly increased with a lower Noxa level, compared with normal ECa9706 cells. Cisplatin 5 μM could cause proliferation inhibition, G2/M phase arrest and apoptosis in ECa9706-CisR cells and these effects could be enhanced dramatically by SIRT1 silencing. Moreover, Noxa expression was increased after treated with SIRT1 siRNA. Conclusions: Over-expression of SIRT1 may cause resistance of ESCC cells to cisplatin through the mechanism involved with Noxa expression.